Діалектизми як засіб увиразнення текстів Мирослава Дочинця - Микитюк, Оксана; Mykytyuk, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано, як внаслідок політики лінгвоциду й етноциду діалектний простір було зруйновано, а до пасивного запасу потрапила низка лексем. Тому актуальним є вивчення діалектної лексики з погляду етнокультурного збагачення мови. Діалектні особливості творів М. Дочинця схарактеризовано передусім на основі лексики, бо вона відображає ті самобутні риси авторського мовлення, що дають відомості про матеріальну культуру закарпатців (лексичні та етнографічні діалектизми), відтворюють мовлення персонажів, розкривають їхні уявлення про світ, підсилюють виражальні можливості мови, стилістично увиразнюють та емоційно наснажують текст. The article analyzes how as a result of linguocide and ethnocide policy the dialect area was destroyed and passive stock got a number of lexemes. That is why the study of dialect vocabulary from the point of ethnic and cultural enrichment of the language is so important. The article finds out the features of dialect use found in the novels of M. Dochynez:«Vichnyk», «Horyanyn» and «Krynychar» – significant for the present works, which are distinguished by the incredibly lively, rich language, which the author compares with the autumn bunch of grapes that blue sparkles in the sun. The article analyzes the dialectal features of M. Dochynez’ works primarily based on the vocabulary, because it reflects that conversational features of the author’s speech that give information about the material culture of the Transcarpathians (lexical and ethnographic dialecticisms), reproduce the character’s speech, reveal their view of the world, enhance the expressive possibilities of the language, stylistically underline and emotionally inspire the text.
Dialecticisms as a Means of Expressiveness of Myroslav Dochynez’ Texts
Keywords: діалектна лексика; лексичні та етнографічні діалектизми; особливості мовлення письменника; dialect vocabulary; works of M. Dochynez; lexical and ethnographic dialecticisms; specialty of the writer’s speech